2015
DOI: 10.1148/radiol.2015142478
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Inflammation in a Porcine Acute Terminal Ileitis Model: US with a Molecularly Targeted Contrast Agent

Abstract: Purpose:To evaluate the feasibility and reproducibility of ultrasonography (US) performed with dual-selectin-targeted contrast agent microbubbles (MBs) for assessment of inflammation in a porcine acute terminal ileitis model, with histologic findings as a reference standard. Materials and Methods:The study had institutional Animal Care and Use Committee approval. Acute terminal ileitis was established in 19 pigs; four pigs served as control pigs. The ileum was imaged with clinical-grade dual P-and E-selectin-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…US molecular imaging combines the advantages of US with those of molecular imaging by using molecularly targeted contrast agent microbubbles and has been recently translated to first-in-human clinical trials in cancer imaging (20,21). By targeting binding ligands to the microbubble shell that recognize inflammation markers that are overexpressed in patients with IBD such as P-selectin and Eselectin (22)(23)(24)(25), US molecular imaging allows quantitative assessment of inflammation in IBD at the molecular level at various anatomic sites after a single injection of molecularly targeted contrast agent (23)(24)(25)(26). Proof-of-principle studies have shown the feasibility of dual P-and E-selectin-targeted US molecular imaging for assessment of inflammation and excellent correlation with other molecular imaging techniques such as PET and histologic examination and immunofluorescence as reference standards in various rodent models of acute and acute-on-chronic IBD (24,25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…US molecular imaging combines the advantages of US with those of molecular imaging by using molecularly targeted contrast agent microbubbles and has been recently translated to first-in-human clinical trials in cancer imaging (20,21). By targeting binding ligands to the microbubble shell that recognize inflammation markers that are overexpressed in patients with IBD such as P-selectin and Eselectin (22)(23)(24)(25), US molecular imaging allows quantitative assessment of inflammation in IBD at the molecular level at various anatomic sites after a single injection of molecularly targeted contrast agent (23)(24)(25)(26). Proof-of-principle studies have shown the feasibility of dual P-and E-selectin-targeted US molecular imaging for assessment of inflammation and excellent correlation with other molecular imaging techniques such as PET and histologic examination and immunofluorescence as reference standards in various rodent models of acute and acute-on-chronic IBD (24,25).…”
mentioning
confidence: 99%
“…Proof-of-principle studies have shown the feasibility of dual P-and E-selectin-targeted US molecular imaging for assessment of inflammation and excellent correlation with other molecular imaging techniques such as PET and histologic examination and immunofluorescence as reference standards in various rodent models of acute and acute-on-chronic IBD (24,25). Recently, dual-selectin-targeted US molecular imaging has moved from rodent models to a large-animal model of acute ileitis in swine (23). However, to the best of our knowledge, no study has evaluated whether US molecular imaging using clinically translatable dual-selectin-targeted contrast agent microbubbles allows longitudinal monitoring of inflammation in a large-animal model of acute IBD in response to treatment as a next step toward clinical translation of this emerging technology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging the natural pathway of leukocyte rolling on inflamed vascular endothelial cells, a clinically translatable, dual-targeted contrast agent specific for the leukocyte adhesion molecules P- and E-select in has been shown to enable accurate quantification of inflammation in animal models of chemically induced colitis and ileitis. [1011]…”
Section: Application To Molecular Imagingmentioning
confidence: 99%
“…Myocardial ischemia was detected using P-selectin and/or E-selectin targeted microbubbles in a murine model [37], [38], [89], a rat model [90], [91], and a primate model [92]. Additionally, inflammatory bowel disease was imaged using Pselectin and E-selectin targeted microbubbles in a murine model [93], [94] and a swine model [95]. Dual-targeted microbubbles were utilized to further enhance targeting [40], [87]- [89], [91], [92], [94].…”
Section: Molecular Imaging Of Inflammationmentioning
confidence: 99%